Hemodynamics at different levels of salt intake in patients with hypertrophic cardiomyopathy of different age groups - N. G. Poteshkina; N. S. Krylova; M. Y. Maslova; E. A. Kovalevskaya; A. M. Svanadze; G. B. Selivanova (Российский кардиологический журнал)
Aim. To assess the relationship between the level of salt (NaCl) consumption and clinical and hemodynamic parameters in patients with hypertrophic cardiomyopathy (HCM) of different age groups.Material and methods. We examined 57 patients with HCM (mean age, 59,2±16,2 years). The patients were divided into groups according to the World Health Organization (WHO): I — young age (≤44 years old) — 12,4% of patients; II — middle (45-59 years old) — 37,2%; III — elderly (60–74 years old) — 36%; IV — senile (≥75 years old old) — 14,4%. The clinical status of patients was assessed, during which special attention was paid to syncope not related to cardiac arrhythmias. NaCl intake was assessed by the 24-hour urine sodium (Na+) level.Results. In the general cohort, in Na+ level <50 mmol/day, the lowest left ventricular stroke volume (LVSV) index was observed, which were associated with syncope (r=-0,9, p=0,03). With the urinary sodium level of 50-70 mmol/day, an increase in LVSV index was observed and the absence of syncope. At Na+ level more than 70 mmol/day, no increase in LVSV index was observed. In this regard, a predictive model was created, as a result of which it was found that with an increase in Na+ consumption by 1 mmol/day, an increase in LVSV index by 0,3 ml/m2 should be expected. There were no significant differences in the effect of NaCl intake on the studied parameters in patients with HCM of different ages. At the same time, low NaCl intake in elderly patients was associated with syncope.Conclusion. Minimal values of Na+ intake (<50 mmol/day or NaCl 3 g/day) were found, which are unfavorable for patients with HCM due to the risk syncope. The 24-hour urine sodium level to maintain a hemodynamically safe level of LVSV index in patients with HCM should be more than 70 mmol/day (NaCl 4,1 g/day). Monitoring of Na+ consumption level is especially important in elderly people with HCM.